REPRESENTASI FEMINISME DALAM FILM PENYALIN CAHAYA - Mulyani, Try; Handriyotopo, Handriyotopo; Rustim, Rustim (Offscreen, 2024)
This research focuses on the representation of feminism in the film Copyist Cahaya. This film is an interesting study to study because the content in the film contains survivors of sexual violence described by Suryani as a real manifestation of women's struggle for justice and gender equality that she is able to provide evidence of the abuse she experienced. The formulation of the problem in this research is how to represent feminism in the film Pengalin Cahya. This study aims to describe the value of feminism in the Syriac character in the film Pengalin Cahaya. This research uses descriptive qualitative research methods, with a Semiotics analysis approach. The data collection technique used purposive sampling, namely three pieces of the film scene of Copying Cahaya as the primary data. This data analysis technique uses Roland Barthes' semiotics technique which divides semiotics into two stages, namely denotation and connotation. The results of the research in the film Pengalin Cahaya, there is liberal feminism because Suryani is told as a woman who seeks justice starting from herself. The figure of a woman who has strength, a woman who has a leadership spirit, and a brave woman